Influence of pinning centers of different natures on surrounding vortices - Carvalho dos Santos, Rodolfo [UNESP]; Duarte, Elwis Carlos Sartorelli [UNESP]; Okimoto, Danilo [UNESP]; Presotto, Alice [UNESP]; Sardella, Edson [UNESP]; Motta, Maycon; Zadorosny, Rafael [UNESP] (Elsevier, 2023)
Studies involving vortex dynamics and their interaction with pinning centers are an important issue to reach higher critical currents in superconducting materials. The vortex distribution around arrays of engineered defects, such as blind and through holes, may help to improve the superconducting properties. Thus, in this work, we used the time-dependent Ginzburg-Landau theory to investigate the vortex dynamics in superconductors of mesoscopic dimensions with a large central square defect with three different configurations: (i) a hole which passes through the sample (interface with the vacuum); (ii) a superconducting region with lower critical temperature Tc; and (iii) a region with a more robust superconductivity, i.e., with a higher Tc. Such systems can be envisaged as elementary building blocks of a macroscopic decorated specimen. Therefore, we evaluated the influence of different interfaces on the vortex dynamics and their effects in the field-dependent magnetization and time-dependent induced electric potential variation. The results show that the superheating field is independent from the nature of the defect. However, the currents crowd at the vertices of the through hole producing a lower degradation of the local superconductivity, which may increase the upper critical field. On the other hand, the last type of defect can be used to control the vortex dynamics in the main superconducting region around the defect with more accuracy. While the first two defects are attractive for the vortices, the third type is repulsive, being needed several penetrated vortices in the superconducting matrix to allow penetration of vortices into the higher Tc domain.
Keywords: Defects; Superconductivity; TDGL; Vortex dynamics